Implementation of one cycle controller for single phase bi-directional converter - Kannan, R. (Research India Publications, 2017)
The main concern about the bi-directional AC-DC converter is to maintain utility power factor near to unity. One Cycle Controller (OCC) is one of the outstanding control techniques to control these power electronic converters. One Cycle Controller comprises one integrator with reset along with a few linear components like analog comparators, flip-flops, and a clock. This paper presents a hardware implementation of Constant Power Factor-One Cycle Controller (CPF-OCC) which is practiced on the single phase bi-directional AC-DC converter. © Research India Publications.